Acupuncture (Jin’s Three-Needle) versus sham acupuncture in treating mild-to-moderate depression: Study protocol for randomized clinical trial - Hao Wen; Jiafeng Wang; Kaiying Zhang; Na Zhang; Yiqing Shan; Xiaolan Yang; Pengcheng Zhang; Xingyu Xiang; Baoguo Zhang; Chong Zhang (PLoS ONE, 2025)
Background Mild-to-moderate depression is an increasing public health problem worldwide, which is more prevalent than major depression but has received less attention Currently, no existing highly effective pharmacological treatments with minimal adverse reactions are available for this condition. Jin’s Three-Needle Acupuncture (JTN) may be an alternative treatment option for mild-to-moderate depression patients. Methods This is a prospective, parallel-arm, single-blind, randomized controlled trial. We plan to enroll 106 participants with mild-to-moderate depression, randomly assigning them to receive either JTN or sham acupuncture (SA) in a 1:1 ratio. All participants will receive the JTN treatment or SA treatment for 8 weeks (3 per week). The primary outcome will be assessed using the 17-item Hamilton Depression Rating Scale (HAMD-17). Secondary outcomes will include the Self-Rating Depression Scale (SDS), Pittsburgh Sleep Quality Index (PSQI), Hamilton Anxiety Scale (HAMA), Self-Rating Anxiety Scale (SAS), and the Traditional Chinese Medicine Syndrome Score Scale (TCMSS). Evaluations will be performed at baseline and at weeks 4, 6, and 8 after treatment initiation. Statistical analyses will be conducted on both the intention-to-treat (ITT) and per-protocol (PP) datasets. Discussion This study aims to provide high-quality evidence regarding the efficacy and safety of JTN as a treatment for mild-to-moderate depression. Additionally, the mechanisms underlying the effects of JTN in treating mild-to-moderate depression will be explored. Trial registration The trial registered with the International Traditional Medicine Clinical Trial Registry (ITMCTR2024000872). URL: https://www.itmctr.ccebtcm.org.cn